How Soil Covers Can Affect the Dynamics of Temperature, Soil Moisture, and Productivity of Creeping Fresh Market Tomatoes? - Dalbianco, Alessandro Bandeira; Santi, Adalberto; Dallacort, Rivanildo; Fenner, William; Barbieri, João Danilo; Daniel, Diego Fernando; Júnior, Santino Seabra (Journal of Agricultural Studies, 2022)
The aim was to evaluate the influence of soil covers on the dynamics of soil temperature and moisture, canopy air temperature, and yield of creeping fresh market tomatoes. The experiment was carried out in randomized blocks design, using the tomato cultivar Thaise, with 5 treatments, 4 replications, with different soil covers: a) Uncovered soil (conventional planting); b) Mulching (double-sided plastic film - black and white); c) Sorghum; d) Sudan grass and e) Pearl millet), cultivated in Tangará da Serra, Mato Grosso, Brazil. Soil temperature was monitored at depths of 5, 10, 20, and 30 cm and in the crop canopy, using thermocouple sensors of the type "K". Soil moisture was monitored in the 0 to 30 cm layer, using of time-domain reflectometry (TDR) probes. Soil temperature and moisture were evaluated throughout the cycle and, in the end, the total and commercial yield of tomato crop. Soil covers have a positive influence on soil temperature and moisture in the cultivation of creeping fresh market tomatoes so that soil cover with mulching provides the highest soil temperature in the early stages of development and covers with mulching and pearl millet provide the highest values of soil moisture. The highest total and commercial yield of tomato were in the soil cover with mulching, with 110.71 and 75.93 t ha-1, respectively, presenting ideal ranges of temperature and soil moisture, so that the other treatments do not differ from each other, with the average total yield of 91.45 t ha-1.